Narrating student life in a time of risk - Rau, Asta; Coetzee, Jan K.; Vice, Amy (Qualitative Sociology Review, 2010)
Students speaking to students reveal how they perceive and experience risk — and specifically, risk associated with HIV — during their years attending a small university in the Eastern Cape Province of South Africa. Data were collected in twenty focus group discussions that spanned two years and two cycles of an action research project designed to infuse HIV/AIDS-content/issues into a closely supervised third-year Sociology research methodology course. The project was undertaken in response to a call by HEAIDS (Higher Education HIV/AIDS Programme, funded by the EU) for universities to address HIV/AIDS in curricula. The intention is to prepare young graduates to respond meaningfully to HIV and AIDS when they enter the world of work in a country with alarmingly high levels of HIV prevalence and incidence. Insights from theorists Ulrich Beck (1992) and Mary Douglas (1986) on the cultural dynamics of modernity were used as lenses to view the narratives of students in relation to three key HIV risk factors: alcohol consumption, multiple and concurrent sexual partnerships, and condom use. Gender, which emerged as a cross-cutting issue, was also explored. The rich qualitative data were brought into a dialogue with selected statistics from the HEAIDS 2010 sero-prevalence survey conducted in 21 higher education institutions in the country. Data show that risk perception and risk behaviour are formulated at individual, social network, and societal/structural levels — as well as at the interface between these. Understandably there was variation in how individual students perceive, experience and negotiate risk, but overall, participating students assessed risk in terms of its immediate importance or threat to them, prioritising the now and choosing not to think about the future. Social bonding, including peer pressure, exerts considerable influence on the ways in which students construct and re-construct their perceptions of risk, and HIV/AIDS. From a structural perspective the smallness of the university and the town lulls students into trusting easily and believing that greater visibility leads to greater safety. Sex is “no big deal” and casual sexual relationships are accepted by many as the norm. Although students report high condom use in casual sexual encounters, which mitigates risk, condom use drops sharply in the context of alcohol consumption — and the often excessive consumption — which is “the order of the day”. Overall, patterns in risk perception and behaviour suggest that many student participants feel justified — by virtue of being students and free at last to explore and experience the edges of their adult life — to push the boundaries of risk.